Microcomputers in a library environment: the experience of library, Faculty Of Egineering - Lee, A. (University of Malaya Library, 1989)
Describes the experiences of the Library at the Faculty of Engineering, University of Malaya with the microcomputers and the benefts derived from it. Describes the initial use of DBase III+ and later CDS/ISIS to create the library's catalogue, academic exercises, acquisition processes, and current awareness services.